HUBUNGAN RELIGIUSITAS DENGAN PENYESUAIAN DIRI SISWA PONDOK PESANTREN - Ahmad Isham Nadzir; Nawang Warsi Wulandari (University of Merdeka Malang, 2013)
The purpose of this study was to examine the association of religiosity with the adjustment to the boarding school students. The hypothesis of this study was the relationship of religiosity on adjustment. The research samples are 132 students of Madrasah Aliyah boarding Rasyidiah Khalidiah Amuntai. Sampling technique use proportional stratified sample. Methods of data collection using the Likert method, the details as much as 60 item religiosity scale and scale adjustment of 60 items. The validity of the test results using the correlation of Pearson Product moment where religiosity scale showed a fall item 8 and 52 item valid with a correlation coefficient of 0.301 to 0.737 moving with a significance level of 5%, while the scale of adjustment showed a fall item 7 and 53 item valid with a correlation coefficient of 0.301 to 0.541 moving with a significance level of 5%, the results of reliability testing two variables using the formula of Cronbach Alpha coefficient indicates reliabilities of 0.884 to 0.935 for the adjustment and religiosity, which shows a second measurement scale is reliable and very reliable. The results of the data analysis using product moment correlation showed that the count r = 0.511 and r = 0.172 in table 5% significance level at which a count r 0.511 0.172 r table means the hypothesis is accepted.